2020
DOI: 10.3389/fendo.2020.00503
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Muscle Size and Density With Proximal Femur Bone in a Community Dwelling Older Population

Abstract: Conclusions: We observed positive associations of the gluteus and thigh muscle size with proximal femur volumetric BMD. Specifically, the gluteus maximus muscle CSA was associated with trochanter cortical vBMD in both men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
4
10
0
Order By: Relevance
“…The present results showed that the PDFFs of several muscles were negatively associated with the aBMD of subregions of the proximal femur as follows: the G.MaxM was negatively associated with the aBMD of the FN, TR, and IT; the G.MedM was negatively associated with the aBMD of the TR and IT; and the IliopM was negatively associated with the aBMD of the FN, TR, and IT. Lu ( 32 ) found that the lipid infiltration of the G.MaxM and mid-thigh muscle is associated with the aBMD of the proximal femur, which agreed with the present study. Intramuscular fat infiltration impairs the ability of the skeletal muscle to produce normal protein, resulting in decreased insulin sensitivity.…”
Section: Discussionsupporting
confidence: 92%
“…The present results showed that the PDFFs of several muscles were negatively associated with the aBMD of subregions of the proximal femur as follows: the G.MaxM was negatively associated with the aBMD of the FN, TR, and IT; the G.MedM was negatively associated with the aBMD of the TR and IT; and the IliopM was negatively associated with the aBMD of the FN, TR, and IT. Lu ( 32 ) found that the lipid infiltration of the G.MaxM and mid-thigh muscle is associated with the aBMD of the proximal femur, which agreed with the present study. Intramuscular fat infiltration impairs the ability of the skeletal muscle to produce normal protein, resulting in decreased insulin sensitivity.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is relevant because as IMAT increases, muscle quality, and possibly muscle function, decreases ( 43 ). Moreover, the frequently occurring low muscle mass at legs level and reduced thigh cross-sectional muscle area are known to be associated with reduced bone mineral densities, in line with a previous report ( 44 ), underscoring the relationship between bone and skeletal muscle in elderly osteoporotic women.…”
Section: Discussionsupporting
confidence: 88%
“…Participants were anthropometrically measured in age of 31 and 46, and what is more in age of 46 their body composition was measured and lumbar MRI was performed to calculate surface area of lumbar vertebrae. Results suggest that from anthropometric measures, height and lean body mass have the most notorious correlation with surface area of vertebrae [15]. In Beijing Jishuitan Hospital relationship between Bone Mineral Density of femur, lumbar vertebrae and iliac bone and density of surrounding muscles was verified using CT in group of women.…”
Section: Muscle Mass and Fracturesmentioning
confidence: 92%